Perioperative Nutrition - Marek Nalos (Indonesian Nutrition Association, 2022)
Modern perioperative care is making steady advances in achieving optimal recovery for patients using the concept of early recovery after surgery (ERAS). Perioperative nutrition plays an important part in ERAS care and opportunities for nutritional interventions present for weeks up to hours before an operation, as well as in the postoperative period. Despite that malnutrition and suboptimal nutrition in surgical patients, particularly in those presenting with cancer, is very common.